Examining The Importance of Leadership Skills in Todays Life - Anel Nailul Muna (International Journal of Social Service and Research, 2022)
Leadership is indeed a classic topic of discussion, it is very old, but it is still very interesting to discuss because it determines the continuity of an organization. Leaders are the most important element in the general management process. Whether or not the results achieved by an organization are determined by the ability of a leader in carrying out their duties. Leadership is the key to moving a community, business and other organization. Starting from leading yourself, leading others and leading an organization. Generation Z if they don't have leadership skills are like humans, rich in ideas but poor in action. Leadership in an organization/institution has a very important role, because without leadership, the goals of educational institutions that have been carefully planned will not be achieved, besides that good leadership must be synergized with perfect and orderly management. This study uses a qualitative research method with a literature study and documentation approach. The results of the study indicate that the criteria that leaders must possess are visionary, innovative, the ability to create vision, ability, communication, ability to provide motivation, ability to direct, ability to make decisions, ability to foster, and have 3 dimensions of skills namely Intelligence, Personality, Abilities.